Climatic change and diet of the pre-Hispanic population of Gran Canaria (Canary Archipelago, Spain) during the Medieval Warm Period and Little Ice Age. (April 2021) - Lécuyer, Christophe; Goedert, Jean; Klee, Johanne; Clauzel, Thibault; Richardin, Pascale; Fourel, François; Delgado-Darias, Teresa; Alberto-Barroso, Verónica; Velasco-Vázquez, Javier; Betancort, Juan Francisco; Amiot, Romain; Maréchal, Chloé; et al.
Abstract: The hard and soft tissue remains of a pre-Hispanic population of the Gran Canaria Island at six different archaeological localities were studied using 14 C dating and stable isotope compositions. Radiocarbon dating indicates island occupation ranging from the beginning of the 7th to the mid-14th century. We analyzed the oxygen isotope compositions of apatite phosphate bones of some pre-Hispanic individuals. The oxygen isotope compositions of meteoric water (δ 18 Ow ) show a significant decrease from −2.1 ± 1.5 to −4.4 ± 1.2‰ (VSMOW) from the Medieval Warm Period (MWP) to the Little Ice Age (LIA). This is interpreted to reflect a decrease in air temperature by about 5 ± 3 °C. Archaeological data along with δ 13 C, δ 15 N and δ 34 S values of soft tissue indicate that the pre-Hispanic population from Gran Canaria relied on agriculture throughout the 7th to mid-14th century. However, a significant contribution of seafood to the diet of the pre-Hispanic population is observed at archaeological sites located close to the shore. These results suggest cultural resilience in the pre-Hispanic population of Gran Canaria, reflected in the relative constancy of their diet in light of climate change. Highlights: 14 C dating reveals Gran Canaria occupation by humans from 7th to 14th century. δ 18 O of human apatite suggest air temperature decrease by 5 ± 3 °C during the LIA. δ 13 C, δ 15 N and δ 34 S of bone collagen were used to reconstruct human diet. Canarios mainly relied on agriculture throughout the 7th to mid-14th century. During the LIA, Canarios started to consume significant amounts of marine food.